The Allies and the German Problem, 1941-1949 From Cooperation to Alternative Settlement - Szanajda, Andrew; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
The Allies and the German Problem, 1941-1949 examines Allied policymaking during the Second World War and the military occupation of postwar Germany, demonstrating how the initial unity of the Allies disintegrated during the postwar military occupation in the face of their separate goals for postwar Germany and Europe.
Keywords: Military history; World politics; World War, 1939-1945.; Europe—History.; History, Modern; Europe, Central—History.; History of Military; Political History; History of World War II and the Holocaust; European History; Modern History; History of Germany and Central Europe